Antigen Processing for MHC Class II Presentation via Autophagy - Munz, Christian (Frontiers in Immunology, 2012)
T cells recognize proteolytic fragments of antigens that are presented to them on major histocompatibility complex (MHC) molecules. MHC class I molecules present primarily products of proteasomal proteolysis to CD8+ T cells, while MHC class II molecules display mainly degradation products of lysosomes for stimulation of CD4+ T cells. Macroautophagy delivers intracellular proteins to lysosomal degradation, and contributes in this fashion to the pool of MHC class II displayed peptides. Both self- and pathogen-derived MHC class II ligands are generated by this pathway. In addition, however, recent evidence points also to regulation of extracellular antigen processing by macroautophagy. In this review, I will discuss these two aspects of antigen processing for MHC class II presentation via macroautophagy, namely its influence on intracellular and extracellular antigen presentation to CD4+ T cells.